Speed and socioeconomic development: Influence of Indian railways - Neelakantan Ravi (Asian Development Bank Institute (ADBI), 2019)
Indian Railways is a little over a century and a half old. Its development over the decades has been gradual. It has been and continues to be the "lifeline for the socioeconomic growth of India," by connecting human settlements across the country and simultaneously transporting various resources to centers of production and markets. Nationalized in 1951, Indian Railways is among the largest rail networks in Asia and the world's second largest network operated under a single management. We will feature its growth over the past 7 decades. Indian Railways has always aimed to provide safety during travel. The rate of its development as a service organization has been modest, with two forces, one originating from political considerations balanced by another based on engineering competence. High-speed rail travel emerged in Indian Railways in 1969, when the first high-speed limited-stop train service was introduced between New Delhi and Kolkata. We will trace the origins of high-speed travel on Indian Railways and attempt to show how it has indeed helped passengers reach their destinations in less time. Any direct correlation between high-speed train travel and the growth of the economy, the effect on the environment and society, while significant over the long term, would be difficult to estimate empirically. We will show, in terms of policy flow and implications, how Indian railways has been unwavering in providing sustenance for economic growth. One common theme in these decades has been the inexorable drive to acquire and develop technology to ensure faster, inexpensive, and safer travel for all users. The increase in speed of travel has been steady, progressive, and not an attempt at creating records. Over the years, high-speed trains have enabled better quality of life for professionals in India, especially in the age of globalization. However, the effect of this has been generally restricted to medium distance and suburban travel. In this scenario, we will detail the steps that have to be taken by the provider and the user for making future high-speed rail travel profitable, productive, comfortable, and dependable.
Keywords: O2; O53; R48; 330; high-speed rail; Indian Railways; socioeconomic development; train; travel